Data from: Root phenology unresponsive to earlier snowmelt despite advanced aboveground phenology in two subarctic plant communities - Blume-Werry, Gesche; Jansson, Roland; Milbau, Ann (Zenodo, 2018)
Earlier snowmelt at high latitudes advances aboveground plant phenology, thereby affecting water, nutrient and carbon cycles. Despite the key role of fine roots in these ecosystem processes, phenological responses to earlier snowmelt have never been assessed belowground. We experimentally advanced snowmelt in two contrasting plant community types, heath and meadow, in northern Sweden and measured above- and belowground phenology: leaf-out, flowering and fine root growth. We expected earlier snowmelt to advance both above- and belowground phenology, and shrub-dominated heath to be more responsive than meadow. Snow melted on average nine days earlier in the manipulated plots than in controls, and soil temperatures were on average 0.9 C higher during the snowmelt period of three weeks. This resulted in small advances in aboveground phenology, but contrary to our expectations, root phenology was unresponsive with root growth generally starting before leaf-out. These responses to the snowmelt treatment were similar in both plant community types, despite strong differences in dominating plant functional types and root properties, such as root length and turnover. The lack of a response in root phenology, despite warmer soil temperatures and aboveground phenological advances, adds evidence that aboveground plant responses might not be directly translated to belowground plant responses, and that our understanding of factors driving belowground phenology is still limited, although of major importance for water, nutrient and carbon cycling. aboveground_phenology 'phen' = phenological stage (2=first leaf, 3=first flower) ANS_Air_temp Air temperature data from Abisko Scientific Research Station (for figure S2) root_growth 'growth area' is root growth mm per observed (minirhizotron) area (i.e. response variable) root_length root length at the end of the experiment, 'plotnr' is block of two paired plots (Tubes) snowdepth snowdepth, measured as described in manuscript snowmelt_doy day of year of melt-out soiltemperatures ...